Properties modeling of cement composites made of fly ash - Dragica Jevtić; Dimitrije Zakić; Aleksandar Savić; Aleksandar Radević (Zaštita Materijala)
There is a number of advantages when using fly ash in cement composites. Fly ash is known for decades for its' pozzolanic properties, and thus it is mostly used as an mineral admixture in the process of production of cement. This way benefits like saving energy and reduction of CO2 emission are obtained. This paper presents the results of research conducted on cement composites made with fly ash from Serbia, added as a partial substitute for cement. The properties of fresh and hardened cement composites were studied with replacement of different mass quantites of cement. Studies have shown that with the moderate amount of fly ash (up to 30%) it is possible to obtain satisfactory physical and mechanical properties of cement composites, both in fresh and hardened state.